Our experience of nifedipine as a tocolytic agent in preterm labor (24 weeks to 36 weeks 6 days) - Hangekar, Parag M.; Karale, Anand; Risbud, Neelesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm birth is defined as birth between the age of viability and 37 completed weeks of gestation. The aim of this study is to evaluate the safety and efficacy of nifedipine, a calcium channel blocker, as a tocolytic in prolonging duration of pregnancy in case of preterm labor. Methods: This is a retrospective analytical study conducted in Department of Obstetrics and Gynaecology, SKNMC and GH, Pune, India conducted over a period of one year from June 2014 to May 2015. All uncomplicated, singleton preterm labor cases were given Cap. Nifedipine as tocolytic and Inj. Betamethasone for enhancing fetal lung maturity. Maternal parameters studied were Gravida and Parity, previous history of preterm labor, gestational age at delivery, mode of delivery, side effects. Neonatal parameters studied were weight at birth, APGAR score at birth, complications at birth, NICU admissions, mortality. Results: Out of total 4478 deliveries from June 2014 to May 2015, 252 women with preterm labor were treated with nifedipine. 214 out of 252 delivered at term with overall success rate of 84.92%. Out of remaining 38 cases, 36 cases delivered as preterm normal deliveries and 2 required Caesarean section. No major side effects observed in mothers receiving nifedipine. As regards neonatal outcome, 12 babies required NICU admission and mortality was of 2. Conclusions: Nifedipine is safe and effective in prolonging preterm labor and has minimal maternal and neonatal side effects. It eliminates the need for intensive maternal monitoring as required in case of betamimetics.